Coptic Egypt History and guide - Jill Kamil (Cairo American University, 1990)
Ill., cart. geo.
Copti
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018